Lokakarya Kepala Sekolah Penggerak dalam Mengembangkan Kepemimpinan Pembelajaran di Kabupaten Seram Bagian Barat - Syamsuar Hamka (IAIN AMBON, 2023)
Effective learning leadership is a crucial factor in improving the quality of education in West Seram District. To encourage the growth of effective learning leadership, the headmaster's strategic role is needed in initiating innovation and facilitating the development of leadership competencies for teachers and education personnels. As part of the ‘Penggerak’ Schools program, the Balai Guru Penggerak (BGP) conducted headmaster leadership workshops. This workshop is a meeting between school supervisors facilitated by the Facilitator of the ‘Penggerak’ School within the West Seram district to discuss how headmasters as learning leaders are able to map and improve teacher competencies to realize liberating learning. This workshop involved the active participation of school principals as well as teachers from the Learning Committee Board (DKP). Activities in the workshop include discussions based on current issues in education, effective strategies for building an inclusive learning culture, and ways of managing resources to support best learning practices. In addition, the participants also shared their experiences and views on the challenges and opportunities that exist in West Seram Regency, enabling them to learn from each other and find collaborative solutions. The results of this workshop demonstrated an improvement in principals' understanding of the importance of student-focused learning leadership. The participants also improved their skills in developing action plans to address specific educational problems in their schools. In addition, the workshop also created a collaborative network between principals and related educational institutions, facilitating information exchange and ongoing support in efforts to improve the quality of education in the regency.Keywords: Leadership Workshops, Headmasters, ‘Penggerak’ Schools